Association between PM2.5 and skin redness features in Taiwan. - Fu-Yu Chan; Chia-Pin Chio; Tzu-Hsuen Yuan; Shu-Fang Shih; Chao-Jen Shih; Chang-Chuan Chan; Yaung-Chuan Lee; Chie-Chien Tseng (PLOS Global Public Health)
Air pollution, particularly fine particulate matter (PM2.5), has been associated with various health issues, but its effects on skin health, specifically skin redness, remain underexplored. This study aims to examine the relationship between PM2.5 exposure and skin redness, with a focus on the role of sebum production in different age groups. A total of 472 participants from two communities in Taiwan in two age groups (20-59 years, n=240; over 60 years, n=232) were included in the study. PM2.5 exposure levels were estimated using land use regression models based on participants' residential addresses. Skin redness area was assessed using the VISIA Imaging System. Linear regression analyses were conducted to examine the association between PM2.5 and redness area, adjusting for demographic, lifestyle, and ultraviolet exposure. Results showed a significant positive association between PM2.5 levels and redness area in both age groups. In the 20-59 age group, each unit increase in PM2.5 corresponded to a 1.70-unit increase in redness area (95% CI: 0.32 - 3.07, p < 0.01), while in the over-60 group, the increase was 2.63 units (95% CI: 1.19 - 4.08, p < 0.001). Additionally, porphyrins showed a positive association with redness area among the 20-59 age group (p < 0.05), while no significant association was found in the over-60 group. This study suggests a linkage between PM2.5 exposure and skin redness area, indicating that air pollution may be a contributing factor to skin health issues. The findings suggest that the interaction between lipophilic and carcinogenic substances in PM2.5 and porphyrins could elevate redness area levels and potentially increase the risk of chronic skin conditions and skin cancer.